2020
DOI: 10.1111/jocs.14857
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic surgery during the Covid‐19 pandemic: Perioperative care, safety, and surgical results

Abstract: Background Covid‐19 was declared a pandemic by the World Health Organization (WHO) on 11 March 2020. Responses to this crisis integrated resource allocation for the increased amount of infected patients while maintaining an adequate response to other severe and life‐threatening diseases. Though cardiothoracic patients are at high risk for Covid‐19 severe illness, postponing surgeries would translate to increased mortality and morbidity. We reviewed our practice during the initial time of the pandemic, with emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A 4-month-old baby with a cardiac teratoma was reported to undergo heart surgery 2 weeks after testing positive for COVID-19 with no complications. 10 Berkhordari et al reported that 21 out of 25 patients with COVID-19 who underwent heart surgery, mainly coronary artery bypass grafting, had smooth respiratory outcomes. 11 However, neither of these procedures required leaving a foreign body in the blood stream as with our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4-month-old baby with a cardiac teratoma was reported to undergo heart surgery 2 weeks after testing positive for COVID-19 with no complications. 10 Berkhordari et al reported that 21 out of 25 patients with COVID-19 who underwent heart surgery, mainly coronary artery bypass grafting, had smooth respiratory outcomes. 11 However, neither of these procedures required leaving a foreign body in the blood stream as with our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Limited information has been reported regarding patients undergoing necessary or urgent procedures in the setting of a recent COVID‐19 infection. A 4‐month‐old baby with a cardiac teratoma was reported to undergo heart surgery 2 weeks after testing positive for COVID‐19 with no complications 10 . Berkhordari et al reported that 21 out of 25 patients with COVID‐19 who underwent heart surgery, mainly coronary artery bypass grafting, had smooth respiratory outcomes 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The research article analyses of surgical outcomes allow evaluating the clinical outcomes of patients undergoing urgent or serious surgeries during the COVID-19 pandemic. It was established that the average duration of hospitalization among surgical COVID-19 patients was 10.55 d[ 24 , 25 ]. Once again, the main question in this pandemic situation remains the surgical outcomes in patients with COVID-19 infection[ 26 ].…”
Section: Surgical Complications and Outcomes In Covid-19 Patientsmentioning
confidence: 99%
“…In addition to this finding, the prevalence of acute renal failure is highlighted, as well as the longer hospital stay between the groups. The changes and protocols initiated by several surgical services for the care of COVID-19 patients were important in the pandemic, as described by Casanova et al [ 2 ] , with the objective of reducing the spreading of the infection and its inherent complications.…”
mentioning
confidence: 99%